Memes as Discourse: A Multimodal Analysis of Humor and Ideology on Social Media - Aditya Raffa Nanda; Jovan Morientes Nigel; Naya Islah Nabilah; Samuel Sihombing (Jurnal Pendidikan dan Sastra Inggris, 2026)
In the contemporary landscape of digital communication, memes have evolved into a medium of expression that extends beyond mere entertainment, playing a significant role in shaping social discourse, identity, and ideology on social media. This phenomenon has become increasingly relevant amid the intensity of digital interactions, where humor is often employed to implicitly convey criticism, emotions, and social positioning. This study aims to understand how memes are interpreted as multimodal discursive practices that represent humor and ideology within the experiences of social media users. A qualitative approach with an interpretative case study design was employed to explore participants’ meanings and experiences in depth. Data were collected through in-depth interviews, digital observation, and document analysis of memes circulating on social media platforms, involving 15–20 active participants aged 18–35 years. Data analysis was conducted using thematic analysis integrated with a multimodal critical discourse analysis approach. The findings reveal three main patterns: humor as a “safe” expressive strategy for conveying social anxieties, ambivalent experiences characterized by tension between laughter and moral discomfort, and the use of memes as performative tools for constructing digital identity. These findings indicate that memes constitute complex spaces of meaning negotiation, where expression, ideology, and social control interact dynamically. Theoretically, this study enriches the field of Critical Discourse Analysis by incorporating the dimension of users’ subjective experiences. Practically, it provides important implications for strengthening critical digital literacy and enhancing the understanding of social communication in the digital media era.